Manifest west: transitions and transformations - Todd, Mark, author; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2018)
Volume 7, Manifest West Series, Western Press Books What changes, alters, undergoes renewal or metamorphosis in the West? The space shared and sparred-over in urban Oregon versus remote Colorado casts doubt on the concept of a true continuity to the west. Where and when do those frontiers, borders, or alterations in course occur? Each watershed and microclimate is a slight shift from the next, each city center and community hall a locus of both change and tradition, and the emotional landscapes can be as dramatic or serene as those on the map. Language can do some of the work of capturing that flux: tracking transition and transformation to get at the heart of a life lived. The poems, short stories, and creative nonfiction essays collected here raise as many questions as they answer about that often fraught, always exciting liminal space between the proverbial here and there, the now and now again. Manifest West is Western Press Books' literary anthology series. The press, affiliated with Western State Colorado University, produces one anthology annually and focuses on Western regional writing.
Transitions and transformations
Ars poetica; Springs without rains / Jessica McDermott -- Like the sun over primeval Earth / Jared Smith -- Cardiolesque (Phoenix, 2015); the cloud of unknowing / Cynthia Hogue -- Blue windows / Rick Kempa -- Gunnison Gorge / Tim Weed -- Mother, anthropologist; Disclosure: / Kierstin Bridger -- Hushed voices / Rick Kempa -- YUAN: the origin of a family name / Yuan Changming -- Shopping for light / David Lavar Coy -- Baseline / Caitlin Horrocks -- Like a living thing / Lisa Levine -- Saving Brownie / Tim Donovan -- No. 6; No. 13 / Mark Haunschild -- Midwestern Abecedarian / Andrea England -- December apples / Susan Brown Weitzman -- Main Street revitalization / Scott Siegel -- Ponderosa / Eric Aldrich.
A literary anthology 2018
Keywords: West (U.S.) -- Literary collections; Western stories; Short stories, American; American poetry